EFFECT OF PRODUCT KNOWLEDGE AND BRAND IMAGE TO PURCHASE INTENTION WITH HP LAPTOP BRAND PRICE DISCOUNTS AS VARIABLES MODERATED IN SURABAYA - Mendrofa, Yoseph Baniader (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
The purpose of this study was to determine the effect of Brand Image on Purchase Intention in Surabaya HP brand laptop. The second objective was to determine the influence of Product Knowledge on Purchase Intention HP laptop brand in Surabaya, and the third goal is to find a role in moderating the influence of Price Discount and Brand Image on Purchase Intention Product Knowledge HP laptop brand in Surabaya. The results suggest that brand image has a significant influence on purchase intention HP brand laptop. Product knowledge has a significant influence on purchase intention on the HP brand laptop. Price discount was not able to significantly moderate the effect of product knowledge on purchase intention HP brand laptop. Price discount was shown to negatively moderate the influence of brand image on purchase intention, but not able to moderate the influence of product knowledge on purchase intention. Giving rebates would have a negative effect on brand image. For that, you should have to pay attention to the provision of rebates to consumers dala addressing the psychological linkage between the image of the product caused by the price.